C-reactive protein to rule out complicated pneumococcal disease manifestations: a retrospective cohort study in adults with pneumococcal bacteraemia - Milou J.V. Serbée; Elisabeth A. Dulfer; Kirsten K.T. Dirkx; Ron Bosboom; Bas Robberts; Heiman F.L. Wertheim; Bert Mulder; Marien I. de Jonge; Carel F. Schaars; Caroline M.A. Swanink; Amelieke J.H. Cremers (International Journal of Infectious Diseases, 2021)
Objectives: To explore the negative predictive value (NPV) of C-reactive protein (CRP) at admission to exclude complicated disease manifestations of pneumococcal disease.Methods: A Dutch multicentre retrospective cohort study was conducted between 01-01-2012 and 30-06-2020. Adults with positive blood cultures for Streptococcus pneumoniae, whose CRP was measured at admission and whose infection focus was known, were included. Electronic medical and microbiological records were reviewed.Results: Of the 832 bacteraemic patients enrolled, 30% had complicated manifestations of pneumococcal disease; most frequent were pleural effusion (8.9%), pleural empyema (5.4%) and meningitis (7.5%). Compared to solitary pneumonia, patients with pleural effusion and empyema presented with higher CRP levels. Although low CRP levels did not exclude complicated disease in general, a CRP level < 114 mg/L at admission could reliably exclude empyema among adult pneumonia patients with an NPV of 93% and a specificity of 26%. However, in cases where pleural fluid was present, CRP levels were mostly > 114 mg/L, such that suspicion of empyema could only be ruled out in a minority of cases (10%).Conclusions: Complicated manifestations are prevalent in adult pneumococcal bacteraemia. Low blood CRP levels can reliably exclude the development of pulmonary empyema. Practical value may be largest in settings without thoracic imaging at hand.